Implementasi Kurikulum Muatan Lokal dalam Mencapai Target Hafalan Al-Qur’an 4 Juz di SD Islam Annajah Jakarta Barat - Fatimah; Sri Tuti Rahmawati (Qiro'ah : Jurnal Pendidikan Agama Islam, 2020)
Many problems faced by the memorizers of the Qur'an such as not being able to memorize correctly according to makhraj and tajwid, there are still many students who have not memorized it perfectly, lack of dividing time in rote repetition, not focus on memorization, That is why it is not easy to memorize the Qur'an. This study aims to determine and describe how the concepts, implementation, evaluation and inhibiting and supporting factors in the Implementation of Local Content Curriculum in achieving the target of memorizing Al-Qur'an 4 juz at SD Islam Annajah West Jakarta. The object of this research is the Principal, Chairperson of the Tahfiz Coordinator, Tahfiz Teachers and students SD Islamic Annajah West Jakarta. Data collection techniques used are interviews, observation and documentation. The steps taken are data reduction, data presentation and conclusion drawing. The results of this study indicate that: (1) The concept of the Tahfiz Al-Qur'an Local Content Curriculum in class I is that students are focused on learning to read the Qur'an and memorizing the surah-An-Nas to Al-Fil, class II is memorizing Al-Qur'an juz 30, class III is memorizing Al-Qur'an juz 29, class IV is memorizing Al-Qur'an juz 28, class V is me-morizing Al-Qur'an juz 27 and for class 6 repeating all memorization from juz 27-30. (2) The implementation of tahfidz is conducted every Monday-Friday. Before students add new memorization ustad / ustadzah recite the verse first, After that students follow together. For students who have memorized it directly deposit the memorization one by one. (3) The evaluation is carried out in several stages in 1 year, namely PTS 1, PAS 1 and PTS 2, PAT 2. Exams are conducted for 3 days, namely Monday, Tuesday and Wednesday. (4) Supporting factors in implementing this program are age, teacher criteria, motivation from parents and teachers, facilities and infrastructure. While the inhibiting factors in implementing the tahfidz program are students, lack of time management, and forgetfulness.